(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This article explores the use of digital platforms by public entities and their interaction with citizens. The investigation is based on a systematic review of recent scientific literature (2021–2025), following the PRISMA method. In the aftermath of the pandemic, the acceleration of digitalization processes has become a hallmark of the contemporary era. Information and communication technologies (ICTs) have emerged as pivotal instruments in fortifying digital governance, enhancing administrative efficiency, and fostering citizen participation. Nevertheless, challenges such as access disparities, digital literacy, algorithmic discrimination, and the absence of comprehensive regulations that ensure the ethical and transparent use of data persist. A comprehensive analysis of 55 academic studies from Latin America, Europe, and Asia was conducted to identify best practices, common challenges, and avenues for enhancement in the implementation of citizen-centered state digital platforms. It has been determined that digital transformation in the public sector must not be regarded exclusively as a technological modernization; rather, it should be regarded as an opportunity to reconfigure the relationship between the state and society. This reconfiguration should prioritize the promotion of digital rights, equity, and effective democratic participation.